Mining-Trading Cryptocurrency dalam Hukum Islam - Zain, Muhammad Fuad (Fakultas Syariah IAIN Purwokerto, 2018)
This paper discusses the mining-trading of cryptocurrency in Islamic law as a digital asset that has recently been traded in cyberspace. The value of cryptocurrency is soaring and fluctuation and it is influenced by the demand of buying and selling. Indodax.com is the official digital asset site in Indonesia that trades more than 13 digital currencies. As we know, digital currencies are not electronic money, even though the characteristic is similar. Starting from this, I analyze whether cryptocurrency is worthy of being value as money that has a certain value. Until now, the Indonesian government through Bank Indonesia has published regulation Number 16/8/PBI/ 2014, which explicitly prohibits using bitcoin and altcoin on financial transactions. Otherwise, MUI (Indonesian Ulema Council) has not issued a fatwa yet related to cryptocurrency. From here, I focuse on this study to the law of cryptocurrency in Islamic law. Bitcoin has advantages and disadvantages. Among its advantages are the user can use exchange or transaction without third service (bank), and it can be traded in merchandise shops. But, the disadvantages of bitcoin are mach more, such as fluctuating value every times, it is not listed as a commodity, it is not watched by Financial Services Authority (OJK), it presents the element of gharar (uncertainty) and maysir (gambling or bet), which makes it possible to be used for money laundering and drugs. On the other hand, until now, the Indonesian people have not considered that bitcoin as a treasure like gold or silver